2017
DOI: 10.1136/jnnp-2017-316329
|View full text |Cite
|
Sign up to set email alerts
|

Staging of cortical and deep grey matter functional connectivity changes in multiple sclerosis

Abstract: Increased connectivity of the deep grey matter became apparent in late RRMS and further increased in SPMS. The additive effect of cortical network degeneration, which was only seen in SPMS, may explain the sudden clinical deterioration characteristic to this phase of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…also incorporate tau aggregation, hypoactivity is also predominant (Marinkovic et al, 2019;Menkes-Caspi et al, 2015). In any case, prevailing evidence of functional imaging in human MS points to altered activity and 10 circuit disconnection (Meijer et al, 2018;Rocca et al, 2010), relating to the findings at the cellular level in our model. Given the profound structural and functional pathology that emerges from a single bout of cortical neuroinflammation, a remarkable observation of our study is the fact that such deficits can be entirely reversible once inflammation subsides.…”
supporting
confidence: 53%
“…also incorporate tau aggregation, hypoactivity is also predominant (Marinkovic et al, 2019;Menkes-Caspi et al, 2015). In any case, prevailing evidence of functional imaging in human MS points to altered activity and 10 circuit disconnection (Meijer et al, 2018;Rocca et al, 2010), relating to the findings at the cellular level in our model. Given the profound structural and functional pathology that emerges from a single bout of cortical neuroinflammation, a remarkable observation of our study is the fact that such deficits can be entirely reversible once inflammation subsides.…”
supporting
confidence: 53%
“…Strictly speaking, an FC change is simply a change in the level of coherence of the affected voxels with the rest of the voxels in the network (Tahedl et al ., 2018). Recent studies have been combining rs-fMRI with other MR modalities to understand FC changes better, and emerging evidence suggests that the direction of FC changes reflects structural damage (Meijer et al ., 2018; Patel et al ., 2018; Tewarie et al ., 2018). Both Patel et al 2018 and Tewarie et al 2018 showed, in their computational modelling studies, that early disconnection mechanisms in the white matter induce increases in functional network connectivity, followed by decreases as structural damage accumulates.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Resting-state functional imaging studies in MS have shown the potential to non-invasively map the intrinsic functional brain networks and to detect early functional brain changes. 6,[10][11][12] Furthermore, graph theory has proved to depict the topological organization of the brain by visualizing the overall connectivity patterns and by characterizing the brain's global organization. 13 Recent studies investigated brain network topology at the CIS stage.…”
Section: Introductionmentioning
confidence: 99%